Morbidity patterns in elderly patients attending medicine department of tertiary care center - Kumar, Vinay; Mital, Pradeep; B., Harshith; Mital, Premlata; Shekhawat, Akshay; Nawal, C. L. (International Journal of Advances in Medicine, 2017)
Background: In India, there is a rapid increase in people above 60 years. In Rajasthan, there is increase in population of persons above 60 years from 5.1% of total population in 1961 to 7.2% in 2011. With increase in their number, the illnesses affecting elderly people will also increase. With this background, this study was done to assess the morbidity patterns in elderly population attending Department of Medicine, S.M.S. Medical College, Jaipur, Rajasthan, India. Methods: This was a cross sectional, prospective and observational study done in medicine department. 250 patients of 60 years and above, attending medical OPD or admitted were included. All data collected were entered in Microsoft Excel sheets and analysed statistically. Results: Respiratory diseases (45.6%) were commonest morbidity followed by cataract (36.8%), cardiovascular (34.4%) and hearing impairment (33.2%). Osteoarthritis was seen in 31.2% and anaemia was present in 20.8%. As the age increases chances of getting morbidities were more. The average number of illnesses per morbid person was 1.92. Conclusions: A high prevalence of morbidity among elderly highlights the urgent need to provide geriatric health care services in the developing country like India. Elderly persons should be motivated to undergo regular health check-ups to identify these common problems at earliest.